Acute mitral regurgitation and cardiogenic shock: Reverse takotsubo cardiomyopathy or acute coronary syndrome?. Issue 6 (December 2021) - DeLago, Augustin J; Morin, Scott J; Ghajar, Alireza; Essa, Mohammed; Pond, Kyle K
Abstract: Reverse takotsubo cardiomyopathy (rTCM) is characterized by basal ballooning and accounts for approximately 1% of all TCM. To our knowledge, there have been no reports describing rTCM complicated by acute, severe, transient mitral regurgitation (MR). A 75-year-old woman with a medical history of hypertension, dyslipidemia, and anxiety presented to the hospital with 2 days of substernal chest pain, dyspnea, and nausea. Initial troponin was 0.203 ng/mL, and electrocardiography showed sinus tachycardia at 121 bpm, with inferior and anterolateral ST segment depressions. Transthoracic echocardiogram (TTE) found an ejection fraction of 30%, apical hyperkinesis, severe hypokinesis of the basal to mid segments of the left ventricle (LV), and a severe central MR jet. Cardiac angiography demonstrated non-obstructive coronary artery disease, and elevated left ventricular end diastolic pressures. Left ventriculography showed a hyperdynamic apex and severe basal hypokinesis. The patient was treated medically, clinical status improved, and was discharged on day 3. TTE four weeks later, showed an ejection fraction of 60–65%, mild MR, and normal LV function. rTCM is the rarest variant of TCM. Basal and mid-myocardial stunning can cause severe secondary MR leading to acute congestive heart failure, mimicking acute coronary syndrome with acute MR. rTCM with rapidly reversible severe MR has not previously been described. <Learning objective: Mitral regurgitation secondary to reverse takotsubo cardiomyopathy can mimic coronary flow obstruction syndromes and when recognized early, can improve with amelioration of cardiomyopathy. Acute severe mitral regurgitation in reverse takotsubo cardiomyopathy is likely secondary to basilar dilatation. Reverse takotsubo cardiomyopathy represents approximately 1% of all takotsubo cardiomyopathy cases.>